2012
DOI: 10.1016/j.ccr.2012.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Overexpression of IL-15 Initiates Large Granular Lymphocyte Leukemia through Chromosomal Instability and DNA Hypermethylation

Abstract: Summary How inflammation causes cancer is unclear. IL-15 is a pro-inflammatory cytokine elevated in human large granular lymphocyte (LGL) leukemia. Mice overexpressing IL-15 develop LGL leukemia. Here we show that prolonged in vitro exposure of wild type (WT) LGL to IL-15 results in Myc-mediated up regulation of aurora kinases, centrosome aberrancies, and aneuploidy. Simultaneously, IL-15 represses miR-29b via induction of Myc/NF-κBp65/Hdac-1, resulting in Dnmt3b overexpression and DNA hypermethylation. All th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
151
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(161 citation statements)
references
References 47 publications
9
151
1
Order By: Relevance
“…However, IL-15 administration may also have untoward consequences. It has been implicated in the pathogenesis of acute lymphoblastic leukemia (35) and large granular lymphocyte leukemia (36). The administration of IL-15 also exacerbates graftversus-host disease after allogeneic bone marrow transplantation (17).…”
Section: Discussionmentioning
confidence: 99%
“…However, IL-15 administration may also have untoward consequences. It has been implicated in the pathogenesis of acute lymphoblastic leukemia (35) and large granular lymphocyte leukemia (36). The administration of IL-15 also exacerbates graftversus-host disease after allogeneic bone marrow transplantation (17).…”
Section: Discussionmentioning
confidence: 99%
“…DCs serve as an important source for IL-15, which is presented to NK cells and enhances their cytolytic function (38,39). We identified a mechanism in human NK cells that allows the regulation of the powerful effect of IL-15 and that might exist to prevent autoimmunity (52). This mechanism seems to be dependent on IL-32a from DCs, as the latter is not induced beyond its basal levels in NK cells in response to IL-15 stimulation (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Regulated provision of transgene IL-15 in this manner may also obviate, or at least reduce, potential adverse events associated with nonspecific overexpression of transgene IL-15 in vivo. [14][15][16][17] We observed that DCIL-15 was superior to rIL-15 in promoting both murine and human DC functionality and therapeutic cancer vaccine efficacy in multiple distinct and clinically-relevant murine tumor models ( 10 , Figs. 1-6 (Fig.…”
Section: -1248-52mentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Unfortunately, high-doses of IL-15 (necessary for its bioactivity in vivo) via systemic administration of recombinant IL-15 protein (rIL-15) or overexpression of transgene IL-15 have untoward side-effects [e.g., stimulating tumor cell growth, activating negative regulators (e.g., programmed death-1) in CD8 C T cells, exacerbating xenogeneic graft-vs.-host-disease or autoimmunity, and functioning as an "oncogene" resulting in progressive CD8 C T or NK leukemia], [13][14][15][16][17] which have served to limit its benefit-to-risk ratio in the clinic, despite pre-clinical findings supporting the safety of rIL-15 in rhesus macaques. 18 IL-15 agonists (e.g., IL-15/IL15Ra-Fc complex and IL-15/IL-15Ra fusion protein) reduce the dose of delivered IL-15 required to reach biologicallymeaningful levels in vivo.…”
Section: Introductionmentioning
confidence: 99%